2001
DOI: 10.1254/jjp.85.189
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety-Like Behavior in Elevated Plus-Maze Tests in Repeatedly Cold-Stressed Mice

Abstract: ABSTRACT-To clarify the relationship between SART (specific alternation of rhythm in temperature) stress (repeated cold stress) and anxiety, the effects of various types of stress on the behavior of mice were studied in elevated plus-maze tests and then the effects of anxiolytics were evaluated. The percentage of time spent in the open arms of the plus-maze apparatus decreased in mice subjected to SART stress without change in the total number of arm entries. No change was noted in mice subjected to other stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 42 publications
(23 reference statements)
5
31
0
Order By: Relevance
“…As in our own previous work and that of others (eg, Griebel et al, 1997;Hata et al, 2001;Khoshbouei et al, 2002), OTR for time was found to be the more consistent and reliable measure of open-arm exploration, and a more sensitive indicator of anxiogenic response to CUS, but similar effects were also seen with OTR for Entries. This combined effect of a decrease in cognitive capability, in particular cognitive flexibility, together with a basal state of anxiety-like behavior induced by CUS is consistent with the changes in cognition and anxiety seen in major depressive disorder.…”
Section: Discussionsupporting
confidence: 84%
“…As in our own previous work and that of others (eg, Griebel et al, 1997;Hata et al, 2001;Khoshbouei et al, 2002), OTR for time was found to be the more consistent and reliable measure of open-arm exploration, and a more sensitive indicator of anxiogenic response to CUS, but similar effects were also seen with OTR for Entries. This combined effect of a decrease in cognitive capability, in particular cognitive flexibility, together with a basal state of anxiety-like behavior induced by CUS is consistent with the changes in cognition and anxiety seen in major depressive disorder.…”
Section: Discussionsupporting
confidence: 84%
“…These doses of WAY 100635 had no significant effect on plus-maze anxiety-like behavior in +/+ controls either in this experiment or in our pilot studies. At the doses presently tested, systemic administration of WAY 100635 and other selective antagonists, such as mPPI, has been found to exert anxiolytic-like effects in the various rodent tasks, including the elevated plus maze, in some studies (eg Cao and Rodgers, 1997a, b;Griebel et al, 1999Griebel et al, , 2000, but not others (eg File et al, 1996;Collinson and Dawson, 1997;Mendoza et al, 1999;Hata et al, 2001; for reviews see Griebel, 1995;Cao and Rodgers, 1997a, b;Griebel et al, 1999). One possible reason for this variability is that the effects of 5-HT 1A receptor antagonists will depend upon basal serotonergic tone and baseline anxietylike behavior evoked in a given test situation, which will vary somewhat across laboratories (Rodgers and Cao, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…These studies have provided insight into the complex roles of CRF 1 and CRF 2 in the regulation of emotional behavior, HPA axis 16) Diazepam, alprazolam and buspirone improved the abnormal and anxiety-like behavior in SART-stressed mice in the EPM test without any influence on unstressed mice. 16) In this study, CRF produced a decrease in the time spent on the open arms in unstressed and SART-stressed mice. a-Helical CRF produced an increase in the time in SART-stressed mice, but had no effect on unstressed mice.…”
Section: Discussionmentioning
confidence: 99%
“…7,12,13) Furthermore, a series of our behavioral studies using SARTstressed animals demonstrated that environmental stress induces anxiety-like behavior. [14][15][16] The anxiety-like behaviors caused by SART stress are normalized by anxiolytic agents such as diazepam, alprazolam, benzodiazepine-receptor agonists, and buspirone, a selective 5-HT 1A serotonin-receptor agonist. [14][15][16] This evidence suggests that SART-stressed animals may be in a state of anxiety.…”
mentioning
confidence: 99%